Pemberdayaan Masyarakat di Kelurahan Bendul Merisi dengan Produksi Eco Enzyme - Ferdinan, Bernardus Aris; Natasya, Chika; Trinitas, Elisabeth Cresentiani; Rosyadi, Jessica Angelia (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The background of the community service program is to provide alternatives to the community regarding household waste management. Waste is a common problem that must be solved together. One alternative to managing waste that can be used as an economical product is the use of eco enzyme. Eco enzyme has several benefits, including: 1) household organic waste will be reduced, 2) eco enzyme products can be used as a substitute for chemical cleaning products, 3) healthier because it is natural, and 4) saving routine family expenses to buy chemical cleaning products. As a result of this community service program, the participants can utilize household waste as raw material for making products with economic value and add creative ideas for future business opportunities.